2018
DOI: 10.2147/ndt.s161377
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and posttraumatic stress disorder in homeless women with mental illness are associated with depression, suicide, and quality of life

Abstract: ObjectiveThis study aimed to determine the following: 1) the proportion of women in the homeless population with schizophrenia (SZ) or bipolar disorder (BD), in addition to the trajectory of their homelessness (ie, homelessness history, number of nights spent without home during the 180 past nights) and the characteristics of their illnesses compared to men (ie, illness severity, suicide risk, physical health status, and quality of life [QoL]); 2) whether these women were victimized more frequently than simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
2
29
2
5
Order By: Relevance
“…Another study found comorbidity between psychiatric conditions and violence among unstably housed women, reporting that those with dual diagnoses experienced higher risk for violent acts [26]. In another study sampling 703 homeless women, those who experienced violent victimization struggled with severe negative mental health outcomes, and often reported poorer quality of life compared to their male counterparts [27]. The study corresponds with our findings where women who experienced sexual assault and had a history of childhood abuse had also reported suicide ideation and negative mental health outcomes.…”
Section: Mental Health-iterated Traumamentioning
confidence: 99%
“…Another study found comorbidity between psychiatric conditions and violence among unstably housed women, reporting that those with dual diagnoses experienced higher risk for violent acts [26]. In another study sampling 703 homeless women, those who experienced violent victimization struggled with severe negative mental health outcomes, and often reported poorer quality of life compared to their male counterparts [27]. The study corresponds with our findings where women who experienced sexual assault and had a history of childhood abuse had also reported suicide ideation and negative mental health outcomes.…”
Section: Mental Health-iterated Traumamentioning
confidence: 99%
“…PTSD in homeless populations is very prevalent [3], specifically in women, with 25.7% in 123 homeless women included in the French Housing First Program [4] suffering from PTSD, versus almost 7% in women of the overall population in France in 2003 [5]. Most studies to date have explored whether homeless people have had an elevated level of exposure to traumatic events and cumulate risk factors which brought on PTSD (e.g., witnessing or being the victim of an attack, sexual assault) [6][7][8], but less is known about the role of homelessness itself as a traumatic experience that leads to exposure to factors predicting PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study exploring the specific mediating effects of mood spectrum signs and symptoms on the relationship between PTSD and intrusiveness, using a path analysis in a clinical sample of subjects exposed to the same isolated severe traumatic event, such as the train crash in Viareggio. Previously, other studies analyzed the potential relationships among traumatic events, PTSD and depression in groups of subjects exposed to completely different types of recurrent or chronic traumatic events, including student military veterans, 43 homeless women with mental illnesses, 44 refugees and asylum seekers, 45 or Korean fire fighters. 46 Other studies highlighted clinical similarities between PTSD and depression, as demonstrated in samples of inpatients with PTSD, 47 community samples, 48 Vietnam veterans, 49 underground train drivers, 50 military members, veterans, and first responders (eg, police, fire, and paramedics) with probable PTSD, 51 or survivors of a chemical warfare.…”
Section: Discussionmentioning
confidence: 99%